Ligature method for the treatment of anal fistula: a modern view on the old approach (literature review) - A. I. Musin (Вестник хирургии имени И.И. Грекова, 2019)
Despite a thousand-year history of anal fistula treatment, long-term outcomes have not been optimal, which encourages us to explore new surgical approaches. One of the methods of surgical treatment of anal fistulas is the use of ligature (Seton) in its different modifications. This review analyzes the literature data on the use of different modifications of seton treatment of anal fistulas. The analysis of publications showed the great interest in the use of the method, yet there is neither clear scheme nor systematic approach to applying it in clinical practice. Further study, as well as randomized researches, are required to find the optimal treatment and improve surgery results of using seton when dealing with anal fistula.